Anatomical and morphometrical approaches on the auditory ossicles in European ground squirrel (Spermophilus citellus) - Martonos, Cristian Olimpiu; Kehl, Melissa; Blagojevic, Milos; Nesic, Ivana; Stan, Florin Gheorghe; Cocan, Daniel; Gudea, Alexandru Ion (Frontiers in Veterinary Science, 2025)
IntroductionThe study of the middle ear and especially the ossicular chain in different species can bring interesting insights into the biomechanics of hearing. The ground squirrel’s middle ear anatomy has not been studied as thoroughly as its other systems and organs.MethodsOur study describes the ear ossicles in this little-studied species, providing the morphological and morphometrical characteristics and a series of comparative data, in an attempt to characterise also some functional anatomy of the incus, malleus and stapes.Results and discussionThe malleus comprises the typical morphological elements, having a round, tuberous head and a very short neck with no bony processes. The manubrium is almost perpendicular to the rotational axis of the ossicle and presents, on its medial surface, the bony process for the insertion of the tensor tympani muscle. Incus is very short and has a deeply incised articular surface for malleus. The lenticular process was identified at the distal part of the long process. The stapes is the smallest ossicle, sheltered in a cavity of the mesotympanic area. It has a very short head, and the stapedial tendon marks its insertion on a visible bony process. An evident surrounding bony ridge marks the elliptic footplate. A comparison of the data related to lever ratio and stapedial surface is also provided based on the collected metrical data.